Learning to be Moved: The Modes of Democratic Responsiveness - Warnick, Bryan; Yacek, Douglas; Robinson, Shannon (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2018)
Being responsive to the experiences, ideas, and stories of others is an essential trait for democratic citizens. Responsiveness promotes the general welfare, it shows respect for others, and allows for what Tony Laden has called the social practice of reasoning. Political theorists have shown how responsiveness is a middle ground between dominance and acquiescence, where citizens show a willingness to be moved by those around them. Responsiveness is tested, though, when citizens interact with those who hold what are thought to be immoral or unjust beliefs. The key question: Is it possible to engage responsively with those who hold morally suspect beliefs, to be legitimately “moved” by those around us, without necessarily acquiescing to the moral problems? We argue that such engagement is both possible and desirable. There are at least five different ways to be moved by others in a productive, civic sense. We describe these modes, explain their moral depth, and give some examples. Civic educators should be aware of these modes and teach students how they can be manifest in democratic life.